The Effect of Memorizing The Quran on Improving Students' Academic Achievement - Tamrin Talebe; Sa’diah Sa’diah; Haerani Harun (Eduvest - Journal of Universal Studies, 2025)
In higher education institutions, the academic achievement of students is an important thing. Various activities and maximizing campus facilities are part of students' efforts to realize their best achievements. Against low academic achievement, a teacher is required to innovate learning and the various approaches used. One strategy that is often recommended by experts is through the strategy of memorizing the Qur'an. As the first step in the learning process, appropriate steps and techniques are needed and support the elements that influence it. The Qur'an and Tafsir Study Program at IAIN Palu has implemented a memorization system for its students to improve their academic achievement and the relationship of memorizing the Qur'an for Students of Qur'anic Science and Tafsir IAIN Palu.